KORELASI ASPEK SOSIAL EKONOMI DENGAN KEJADIAN TUBERKULOSIS PARU PADA PASIEN - Rosdiana, Rosdiana; Fauzi, Ahmad Zil; Kelabora, Jonathan; Suhardono, Suhardono (Ensiklopedia of Journal, 2025)
Pulmonary tuberculosis is one of the infectious diseases that has a significant impact on global public health. This disease is among the ten leading causes of death worldwide. The purpose of this study was to determine the correlation between socioeconomic aspects and the incidence of pulmonary tuberculosis in patients. A case-control study design was used in this study. The study was conducted at the Tanah Jawa Community Health Center in February 2024. The population consisted of all 112 individuals with positive pulmonary tuberculosis. The sample comprised 43 case respondents and 43 control respondents. Simple random sampling was used for sample selection. The research instrument was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a correlation between education (p value: 0.03) and occupation (p value: 0.45) and the incidence of tuberculosis. It is recommended that health centers, especially program officers and infectious disease coordinators handling pulmonary tuberculosis, raise public awareness about pulmonary tuberculosis through non-formal education such as health counseling. Keywords: Work, Education, Tuberculosis